Hithbrto Unknown Imago Caste of Postelectrotermes nayari Roonwal and Verma, 1971 (Isopiera: Kalotermitidae) - Varma, R. V. (Indian Forester, 1977)
The hitherto unknown imago caste of Postelectrotermes nayari is described.